2022
DOI: 10.1080/02670836.2022.2074125
|View full text |Cite
|
Sign up to set email alerts
|

Joining three aluminium alloy sheets by square clinching process

Abstract: The joining of three-layer AL5052-H32 sheets with the square and round clinching process was studied by experimental means. Two 1.5 mm thick and one 2 mm thick AL5052-H32 sheets with three sheet sequences were joined by the square and round clinching process, respectively. The results showed that the square tools can successfully join three sheets in all three sheet orders, while the round tools can effectively connect three sheets only when the thick sheet is at the bottom. Moreover, the strength of the round… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The mechanical characteristics and fatigue characteristics of riveted joints were researched. Besides, Gao et al [27] studied the square and round clinching process for the three-layer Al5052-H32 sheets. In works, different thickness sheets were used.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical characteristics and fatigue characteristics of riveted joints were researched. Besides, Gao et al [27] studied the square and round clinching process for the three-layer Al5052-H32 sheets. In works, different thickness sheets were used.…”
Section: Introductionmentioning
confidence: 99%
“…He proposed a method for achieving a three-layer sheet connection with pre-cut holes in the center sheet when the combination is aluminum, steel, and steel. Gao and Chen 17 conducted an experimental study to examine the connection of three-layer AL5052-H32 sheets with square and round riveting processes.Wiesenmayer et al 18 replaced the top and bottom sheets connected with two half-thickness sheets, and compared the three-layer connection with a two-layer connection connected by a clinching process. Han et al 9 conducted shear and peel experiments with different lap joints of three-layer sheets and analyzed the failure causes and mechanical properties of the joints, and the experimental results showed that the bending effect of the sheets was the main cause of joint failure.…”
Section: Introductionmentioning
confidence: 99%